The Role of Exercise as a Non-pharmacological Therapeutic Approach for Amyotrophic Lateral Sclerosis: Beneficial or Detrimental? - Tsitkanou, Stavroula; Della Gatta, Paul; Foletta, Victoria; Russell, Aaron (Frontiers in Neurology, 2019)
Amyotrophic lateral sclerosis (ALS), a fatal neurodegenerative disease, involves the rapid deterioration of motor neurons resulting in severe muscle atrophy and respiratory insufficiency. It is considered a “multisystemic” disease with many potential mechanisms responsible for its pathology. Currently, there is no cure for ALS. Exercise training is suggested as a potential approach to reduce ALS pathology, but its beneficial role remains controversial. This review provides an overview of the effects of exercise training in ALS-affected mice and patients. It will compare the intensity, duration and type of exercise on the health of SOD1G93A mice, a mouse model of familial ALS, and review clinical studies involving ALS patients undergoing both endurance and resistance training. In summary, mild-to-moderate swimming-based endurance training appears the most advantageous mode of exercise in SOD1G93A mice, improving animal survival and delaying the onset and progression of disease. Furthermore, clinical studies show that both endurance and resistance training have an advantageous impact on the quality of life of ALS patients without extending life expectancy. However, small sample sizes, non-representative control populations, heterogeneous disease stage of patients and the presence of confounders often exist in the exercise studies conducted with ALS patients. This raises concerns about the interpretation of these findings and, therefore, these results should be considered with caution. While promising, more pre-clinical and clinical studies with improved experimental design and fewer limitations are still necessary to confirm the impact of exercise training on the health of ALS patients.